Hoe Afrikaans is Afrikaans-Nederlands?* - Plessis, Hans du (Koers, 1983)
The present position of the leaching of Afrikaans linguistics within a Department of Afrikaans-Nederlands is discussed. Three major problems in the tuition of Afrikaans at the university are identified: (a) an over-emphasis on theoretical linguistics leads to a course in general linguistics rather than a course of Afrikaans;(b) the time and effort devoted to the teaching of Dutch as a major part of the course denies the independence of Afrikaans as a scientific discipline, and(c) the almost total failure to teach Afrikaans as it should be used and is used in everyday speech and writing results in the handing over of graduated students to the profession without their having a proper knowledge of Afrikaans-in-use.